Does the pyramidal ownership mechanism negatively affect the firm’s performance? - Vera Diyanty (Journal of Economics, Business, and Accountancy Ventura, 2016)
This research aims to evaluate the effect of family control, which is obtained through both direct or pyramidal ownership mechanism, and company performance. It also examines the mediating effect of founder leadership as represented by founding family members occupying the top management position and the effectiveness of Board of Commissioner. This study used Ordinary Least Square regression for the data analysis with 670 data as the sample from 134 sample companies from year 2009 to 2013. The results show that family control through direct ownership mechanism enhances company performance (alignment effect). On the other hand, family control through pyramidal ownership mechanism weakens company performance (entrenchment effect). The results also show that founder leadership boosts the alignment effect and limits the entrenchment effect. However, this research fails to confirm the role of the effectiveness of the Board of Commissioner in increasing the alignment effect and limiting the entrenchment effect.